A challenging case on diagnosing Henoch–Schönlein purpura. (July 2020) - Zhang, Lin-Hao; Lan, Tian; He, Du; Wen, Shi-Lei; Tong, Huan
Henoch–Schönlein purpura (HSP) could involve multiple organs, including gastrointestinal tract. It is commonly observed in children, but occasionally also in the elderly. It is challenging to diagnose HSP with delayed purpura. Herein, we report an elderly with HSP, whose non-thrombocytopenic purpura erupted more than 1 month after the first onset of abdominal pain.